Self-efficacy as a determined factor for knowledge sharing awareness - Shaari, Roziana (IACSIT Press, 2014)
This paper discusses the concept of self-efficacy as a factor that can moderates knowledge sharing among academics in public universities in Malaysia. The partial results of survey are presented from the actual study. This paper aims to determine the level of knowledge sharing awareness and to identify whether the approach is associated with demographic factors (designation, gender, working experience and academic field). Participant included 725 academics from 20 public universities. The level of awareness to share knowledge was at moderate level. The One-Way Analysis of Variance (ANOVA) revealed that there were significant differences on the knowledge sharing awareness across designation, working experience and academic field. Significance was not seen between knowledge sharing awareness on gender.